2023
DOI: 10.1001/jamanetworkopen.2023.29147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Nutrition Intervention on Mediterranean Diet Adherence Among Firefighters

Maria Soledad Hershey,
Chia-Rui Chang,
Mercedes Sotos-Prieto
et al.

Abstract: ImportanceUS firefighters are a working population at risk of chronic diseases, including obesity, cardiovascular disease, and cancer. This risk may be mitigated by a healthy diet.ObjectiveTo evaluate the effect of a Mediterranean nutrition intervention using a behavioral/environmental approach (firefighter/fire station/home) at the individual participant level.Design, Setting, and ParticipantsThis 12-month cluster randomized clinical trial included US career firefighters from fire stations and homes within 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In a study conducted on adults, nutrition education was provided through an online platform to increase adherence to the MedDiet. As a result of the study, it was observed that the MedDiet score increased by 2.01 points in the 6th month and 2.67 points in the 12th month [ 52 ]. Considering that the follow-up period in this study was shorter and there was no multidisciplinary training, it is thought that the increase in the Mediterranean diet score is likely to be less.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on adults, nutrition education was provided through an online platform to increase adherence to the MedDiet. As a result of the study, it was observed that the MedDiet score increased by 2.01 points in the 6th month and 2.67 points in the 12th month [ 52 ]. Considering that the follow-up period in this study was shorter and there was no multidisciplinary training, it is thought that the increase in the Mediterranean diet score is likely to be less.…”
Section: Discussionmentioning
confidence: 99%
“…The third level focuses on adopting healthy eating habits and behaviors (i.e., eating out, grocery shopping, frugality, commensality, etc.). Presented as an example of a HLS, the Mediterranean diet and lifestyle were previously encouraged in a nutritional intervention among Midwestern career firefighters in which many website resources have been reutilized ( 28 , 29 ). Despite its cultural and geographic origins, the principles of the Mediterranean diet can be culturally translated and easily adapted in non-Mediterranean populations ( 30 , 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hollerbach et al (2019) reported data from a small study that indicated that FFs who took part in a 10-week online program with individual workout plans and nutritional information had a smaller improvement in body mass index (BMI) than FFs in a control group 7–9 . Recently, a cluster randomized clinical trial including 52 fire stations in the US investigating Mediterranean nutrition intervention reported that the intervention group improved healthy diet adherence after a 12-month intervention in comparison to the control group, which was instructed to follow usual diet 10 . However, given the multifaceted nature of cardiovascular disease, and understanding that adherence to recommended programs and behaviors can be difficult, more research is necessary to understand what types of programming are effective in an occupational setting in order to improve the CM risk profile of FFs.…”
mentioning
confidence: 99%